Modulation of sleep by obesity, diabetes, age, and diet 2026-02-16T06:57:22+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Watson, Ronald R. (Ronald Ross) (Elsevier/AP, Academic Press is an imprint of Elsevier, 2015)

(untitled)
"Sleep disorder is a rampant problem in the US, with over 40 million Americans currently diagnosed according to the NIH. There is a clear association between sleep disorder and a wide range of other human disorders - performance deficiencies, psychiatric illnesses, heart disease, obesity, and more - but in spite of this there is not yet a convenient overview on the market detailing the impact of obesity, age, diabetes, and diet on sleep duration and attendant health outcomes. This volume focuses on the interaction between sleep and these factors, with special attention being paid to the potential for neurological modulation of sleep via diet. The volume aids readers in understanding the role each of these factors plays in sleep architecture and its regulation by circadian biology and neurology"--